2018
DOI: 10.1080/09540121.2018.1496222
|View full text |Cite
|
Sign up to set email alerts
|

Close relationships, individual resilience resources, and well-being among people living with HIV/AIDS in rural China

Abstract: The systems framework of resilience has suggested that resilient factors external to or within the individual and their interactions can contribute to positive adjustment in at-risk populations. However, the interplays of resilience resources at different levels have seldom been investigated in health psychology, particularly in people living with HIV/AIDS (PLWHA). This study aimed to examine the mediating role of individual resilience resources in the associations between marital and family relationships and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
(84 reference statements)
0
18
0
1
Order By: Relevance
“…According to Bodenmann's Systemic Transactional Model (STM) [11], dyadic coping that transpires between couples is a transactional process wherein both partners employ strategies intended to not only help the ill partner but also to maintain equilibrium in their relationship [11,12]. The present literature on dyadic coping shows contradictory findings, with some studies suggesting beneficial roles of partner provided coping, wherein patients experience lower pain [13] and higher resilience [14][15][16], to some studies demonstrating that partners' responses and coping efforts can have negative effects on patients' experience of pain [17] and can cause more anxiety and depressive symptoms [18][19][20]. Although none of these studies have identified direct associations between dyadic coping and patient-related outcomes they do demonstrate that the partner's coping efforts are not always deemed beneficial [21] and may underlie psychological distress [22,23] and marital discord [20] between the couple.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bodenmann's Systemic Transactional Model (STM) [11], dyadic coping that transpires between couples is a transactional process wherein both partners employ strategies intended to not only help the ill partner but also to maintain equilibrium in their relationship [11,12]. The present literature on dyadic coping shows contradictory findings, with some studies suggesting beneficial roles of partner provided coping, wherein patients experience lower pain [13] and higher resilience [14][15][16], to some studies demonstrating that partners' responses and coping efforts can have negative effects on patients' experience of pain [17] and can cause more anxiety and depressive symptoms [18][19][20]. Although none of these studies have identified direct associations between dyadic coping and patient-related outcomes they do demonstrate that the partner's coping efforts are not always deemed beneficial [21] and may underlie psychological distress [22,23] and marital discord [20] between the couple.…”
Section: Introductionmentioning
confidence: 99%
“…Culture can significantly impact psychological adjustments and the social support of patients. Self-adjustment plays a significant self-help role and family and social support are key to the support of patients with infectious diseases ( Huang, et al., 2018 ; Schwerdtle et al., 2017 ). A large number of patients in this study used Chinese cultural idioms while battling the disease, including “The house of goodness will have more celebration.” and “If you don't die, you will have blessings.” This indicated how traditional cultures can promote psychological adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…A settled partnership may enable a couple to support each other to cope with stress from work and daily life, thus improving resilience (Melvin, Gross, Hayat, Jennings, & Campbell, 2012). Improved resilience in the context of high-quality marital relationships is reflected in studies of highly resilient US soldiers (Melvin et al, 2012) and of Chinese HIV patients (Huang, Zhang, & Yu, 2018). Indeed, a high-quality marital relationship was an essential factor in tolerating stress and increasing personal resilience resources (Huang et al, 2018).…”
Section: Resilience and Personal Factorsmentioning
confidence: 99%